2015
DOI: 10.1007/s11738-015-1782-2
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of growth and upregulation of thylakoid membrane proteins in the halophyte Salicornia bigelovii Torr. under saline conditions

Abstract: Salicornia bigelovii is an unusually salt-tolerant plant species and is able to continue to photosynthesize and grow in saline conditions. There is an interest in understanding the mechanisms of this salt tolerance. In this study, S. bigelovii plants grown under 400 mM NaCl had higher growth and higher photosynthetic capacity than those not grown with salt. The intensities of the fluorescence emission peaks in the thylakoid membrane spectra in the salt treatment were higher than in the control. PSII and PSI pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…PT2 comparison. This is in agreement with the results of a previous study of Salicorniabigelovii Torr [ 75 ]. Electrons derived from water by the oxygen-evolving complex of photosystem II are transferred to NADP + , leading to the production of NADPH.…”
Section: Discussionsupporting
confidence: 93%
“…PT2 comparison. This is in agreement with the results of a previous study of Salicorniabigelovii Torr [ 75 ]. Electrons derived from water by the oxygen-evolving complex of photosystem II are transferred to NADP + , leading to the production of NADPH.…”
Section: Discussionsupporting
confidence: 93%
“…The halophytes have a stronger ion regionalization function and, thus, can maintain a higher net photosynthetic rate under salt stress conditions. 100,101 Taking Suaeda salsa as an example, the net photosynthetic rate significantly improved under salt treatment. 102…”
Section: Salt-tolerance Mechanisms Of Seawater Vegetablesmentioning
confidence: 99%
“…Bethke and Malcoln (1992) suggest that the decrease in photosynthetic rate is significantly related to the increase in Na + and Cl – concentrations in the leaves, possibly because the mesophyll cells have insufficient ability to localize these two ions. The halophytes have a stronger ion regionalization function and, thus, can maintain a higher net photosynthetic rate under salt stress conditions. , Taking Suaeda salsa as an example, the net photosynthetic rate significantly improved under salt treatment …”
Section: Salt-tolerance Mechanisms Of Seawater Vegetablesmentioning
confidence: 99%
“…This indicated that salt stress has an adverse effect on PSII and LHC II protein complexes. The strong salt‐tolerant plant Salicornia bigelovii , exhibited better photosynthetic properties under 400 mM NaCl than the control which may be due to an increased amount of psaA/B, CP47, CP43 and LHCb1 with a concurrent increase in antennae size (F. Zhou, Hua, Qiu, Zheng, & Wang, ).…”
Section: Thylakoid Protein Complexmentioning
confidence: 99%